The Commitment of Public Companies in disclosure requirement of Financial Statement: Analysis Study in State Company for Leather Industries (SCLI) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
It has been an increase concern of scientific and professional accounting sides on disclosure especially after appearance of business firms and accounting development with its relationship to financial statements which are considered to be outputs of the activity results.  The preparing of financial statements and auditing of those accounts according to normal principles and standards of accounting on both local and international levels. Accounting disclosure can be seen an importance through discover all fundamental and necessary information for proper supply. Therefore, the research will highlight on public companies commitment in Iraq for basis and standards which have taken disclosure in financial data. The conceptual frame of the research includes concept, kinds, importance and objectives of statements, financial reports and disclosure. On the other hand the practical side includes analysis and studying commitments of public companies requiring disclosure according to accounting basis.The main conclusion of the research that most of public companies have not commitment in giving a complete disclosure according to legal requirements and the law has not imposed on public companies to precise disclosure for all fundamental issues and the weakness of educational programs. The main recommendations of this research, public companies must have provide a complete disclosure according to basis, requirements concerned, reconsider and review internal accounting basis which could be compatible with internal environment and consistence with international standards.